2021
DOI: 10.1111/cbdd.13947
|View full text |Cite
|
Sign up to set email alerts
|

Role of exosomal miRNA in chemotherapy resistance of Colorectal cancer: A systematic review

Abstract: The third most common malignancy has been identified as Colorectal cancer (CRC) that conducive to death in most cases. Chemoresistance is a common obstacle to CRC treatment. Circulating exosomal microRNAs (miRNAs) have been shown to reverse chemo‐resistance and are promising biomarkers for CRC. The capacity of engineered exosomes to cross biological barriers and deliver functional miRNAs could be used to achieve these proposes. The object of this review is the investigation of the role of exosomal miRNA in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…The interaction between tumor cells through exomiRs leads to changes in cellular biological events. This influences the surrounding extracellular tumor matrix environment and ultimately contributes to drug resistance [ 55 ].…”
Section: Exosomal Mirnas Biogenesismentioning
confidence: 99%
“…The interaction between tumor cells through exomiRs leads to changes in cellular biological events. This influences the surrounding extracellular tumor matrix environment and ultimately contributes to drug resistance [ 55 ].…”
Section: Exosomal Mirnas Biogenesismentioning
confidence: 99%
“…MiRNAs act either as oncogenic miRNAs (onco-miRs) or tumor suppressive miRNAs (TS-miRs) with significant tissue- and organ-specificity ( 29 , 30 ). Many studies have also found that miRNAs participate in regulating the drug resistance in CRC ( 31 , 32 ). It has been demonstrated miR-31 negatively regulates breast cancer invasion and metastasis ( 33 ).…”
Section: Mirnasmentioning
confidence: 99%
“…Life 2024, 14, 741 2 of 15 Many studies now demonstrate that radiotherapy and chemotherapy resistance in oral cancers may be mediated, in part, by the expression of microRNAs within these tumors [13][14][15]. These observations are part of a growing body of evidence from other types of cancer, such as breast, ovarian, and colorectal cancers, that demonstrate the key role of microRNAs in mediating cancer development, progression, and response to treatment [16][17][18].…”
Section: Introductionmentioning
confidence: 99%